2020
DOI: 10.1177/2048004020926366
|View full text |Cite
|
Sign up to set email alerts
|

Post-exertional increase in first-phase ejection fraction in recreational marathon runners

Abstract: Objectives Running a marathon has been equivocally associated with acute changes in cardiac performance. First-phase ejection fraction is a novel integrated echocardiographic measure of left ventricular contractility and systo-diastolic coupling which has never been studied in the context of physical activity. The aim of this study was to assess first-phase ejection fraction following recreational marathon running along with standard echocardiographic indices of systolic and diastolic function. Design and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Along these lines, we demonstrated recently that at the peak of HG, the reduction in ejection fraction in healthy subjects is accompanied by higher myocardial work and a better work efficiency index [3]. Moreover, Faconti et al [6] showed a marked increase in EF-1 in recreational marathon runners after a race, despite the lack of increase in the conventional measure of systolic function.…”
Section: Effect Of Afterload Challenge On the First-phase Ejection Fraction And Total Ejection Fractionmentioning
confidence: 73%
“…Along these lines, we demonstrated recently that at the peak of HG, the reduction in ejection fraction in healthy subjects is accompanied by higher myocardial work and a better work efficiency index [3]. Moreover, Faconti et al [6] showed a marked increase in EF-1 in recreational marathon runners after a race, despite the lack of increase in the conventional measure of systolic function.…”
Section: Effect Of Afterload Challenge On the First-phase Ejection Fraction And Total Ejection Fractionmentioning
confidence: 73%